FLASH-RT for pulmonary protection: a comprehensive review of mechanisms, technological advances, and clinical translation - Wen, Yixue; Liu, Xinlan; Zhang, Xiaohong; Long, Li; Feng, Jing; Zhang, Zhen (Frontiers in Oncology, 2025)
FLASH radiotherapy (FLASH-RT), characterized by ultra-high dose rates (>40 Gy/s), has demonstrated remarkable normal tissue-sparing effects in preclinical models while maintaining tumor control. This review specifically focuses on FLASH-mediated pulmonary protection, a critical concern in thoracic oncology. We critically evaluate proposed mechanisms—including oxygen depletion, radical recombination, mitochondrial preservation, DNA integrity maintenance, metabolic modulation, and immune reprogramming—with an emphasis on the strength and limitations of current evidence across in vitro, in vivo, and emerging clinical studies. Additionally, we summarize recent technological advances enabling clinical translation, such as FLASH-compatible beam modalities, real-time dosimetry, and motion management strategies. Unlike previous reviews, we integrate these mechanisms into a unified conceptual model and provide a structured comparison of evidence quality and contradictions. This work aims to clarify current controversies, highlight knowledge gaps, and guide future research and clinical trial design for FLASH-RT–based lung protection.